Negócios jurídicos processuais atípicos no Direito Processual Civil brasileiro: existência, validade e eficácia - Redondo, Bruno Garcia (2019)
This study aims to explore the parties case management powers and atypical contract procedure (without legal provision) within the Brazilian Civil Procedure System. The choice of the subject stems from the need to systematize the study of the plans for the existence, validity and effectiveness of the contract procedure. This paper addresses the issues envolving the requirements and the limits of the parties procedural contracting, and the way that the judge does the judicial control of the customized procedure (procedure tailoring judicial control).The present thesis proposes, therefore, the identification of all validity requirements (expressed and implied), in a systematization that we consider capable of enhancing the use of procedural conventions, diffusing its application in forensic practice